LC-MS/MS based-comparative study of (S)-nicotine metabolism by microorganisms, mushroom and plant cultures: Parallels to its mammalian metabolic fate - Amira R. Khattab; Abdel-Rahim S. Ibrahim; Souzan M. Ibrahim; Kamillia A. Abou El-Seoud; Wafaa E. Soliman; Fathy K. El-Fiky (Faculty of Pharmacy, Cairo University, 2015)
The metabolic fate of nicotine using the cell cultures of microorganisms, mushroom and plants was explored using LC-MS/MS analysis. The study demonstrated parallels to phase I mammalian metabolism of nicotine and reported that nicotine was biotransformed into its N-oxide by Streptomyces fradiae culture. Moreover, it was metabolized in Pleurotus ostreatus culture into nornicotine, norcotinine and β-nicotyrine; whereas, cotinine and its 3'-hydroxylated derivative were the identified nicotine metabolic products in Pimpinella anisum cell culture. However, the microbial culture of Agaricus bisporus bioconverted nicotine into one of its derived-carcinogenic nitrosamines which is "4-(methylnitrosamino)-4-(3-pyridyl)butanal". Mushroom and plant cell cultures were thus proven to be competent to microbial cultures in bioconverting nicotine into many of its previously reported metabolites. Convincingly, the obtained results highlighted the prospect of utilizing other species which are intrinsically-endowed with unique biocatalytic systems, such as mushrooms and plants, in the drug metabolic studies.